Hubungan Prilaku Keluarga Sadar Gizi dengan kejadian Stunting di Sabulira Toba wilayah kerja Puskesmas Ampana Timur, Kabupaten Tojo Una-Una 2026 - Agustiar, Agustiar; Borhan, Jumiati; Fidriana, Ni Luh; Sudirman, Sudirman; Yani, Ahmad (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
Stunting is the failure to thrive in toddlers due to chronic malnutrition, particularly during the first 1,000 days of life (HPK). This condition is caused by prolonged nutritional deficiencies and recurrent infections, influenced by inadequate feeding patterns during the first 1,000 days of life (HPK) (Susilo Wirawan 2022). This study aims to determine the relationship between Nutrition-Aware Family Behavior (Kadarzi) and the incidence of stunting in Sabulira Toba Village. The research used a quantitative approach. This study had a population of 30 and a sample of 30 respondents (total sampling). The results of the study, based on bivariate analysis, showed that statistical tests using the Chi-Square test yielded a P value of 0.001 (<0.05) and a Value of 0.659, indicating a relationship between knowledge and stunting. For attitudes, the Chi-Square test yielded a P value of 0.001 (<0.05) and a Value of 0.714, indicating a relationship between attitudes and stunting. The Chi-Square test for the action variable yielded a P value of 0.001 (<0.05) and a Value of 0.669, indicating a highly significant relationship between nutritional fulfillment measures and stunting in Sabulira Toba Village. The conclusion of this study is that there is a relationship between family knowledge, attitudes, and behavior with stunting. Researchers recommend that families with toddlers adopt a Nutrition-Aware Behavior to prevent stunting in toddlers. Knowledge about nutrition can be obtained from health workers and social media.